Class warriors [videorecording] - Dormer, Mike; Fairley, John; Welfare, Simon (Red Empire presented by Robert Conquent ; series producer, Gruyneth Hughes, 1990)
Covers Stalin's brutality and ruthless dictatorship by starving peasant and factor workers who do not accept his plan for collective farms.